Recognition of unfamiliar predators in domestic horses through only visual predator cues - Rachel Hofacker; Natalie Sebunia; Jessica Pihlblad; Zeynep Benderlioglu (PLoS ONE, 2026)
Acoustic, olfactory, and visual predator cues trigger various adaptive responses among a variety of prey species even when they are under human protection since birth. Previous studies have found that domesticated animals show increased vigilance, stress, flight, and aggregation behaviors in response to predation threats. These investigations, however, did not directly test visual threatening cues alone in animals that communicate more with body language than vocalizations while considering individual temperament and social status. The current study aims to address this issue. Eighteen horses housed at the Ohio State University Equine Center with mixed age and sex were the subjects of the experiments (mean age = 7 years). The horses were shown affiliative and aggressive behaviors of a pack of wolves (unfamiliar predator) and grazing wombats (unfamiliar non-predator) on a projector without any acoustic cues while their reactions were recorded with an equine heart monitor and camera. Data were also collected on assessments of anxiety/fear, social dependency, and social status in the herd. Results showed that domestic horses distinguished an unfamiliar predator from an unfamiliar non‑predator based on visual cues alone, showing significantly higher heart rate (HR) responses to wolf videos than to wombat videos ( P = 0.0022). HR also increased relative to baseline during wolf videos ( P = 0.0005), whereas HR during wombat videos did not differ from baseline ( P = 0.28). There were no significant differences in HR responses to affiliative vs. aggressive behaviors displayed by wolves ( P = 0.4033). The age of the horses was negatively associated with fearfulness ( P = 0.0048) and social dependency ( P = 0.0076). Male horses showed a more heightened HR to unfamiliar predator cues compared to females ( P = 0.0088). High social status was associated with an increased HR response to unfamiliar predator stimuli ( P = 0.033) but was unrelated to control stimulus HR ( P = 0.26), baseline HR ( P = 0.32), fearfulness ( P = 0.26), social dependency ( P = 0.85), age ( P = 0.42), and sex ( P = 0.61). Lateralized gaze revealed a near total absence of left eye viewing across all stimuli, with no difference between right gaze and binocular look durations for wolves ( P = 0.83). In contrast, horses showed a significant binocular preference over right-gaze when viewing wombats ( P < 0.0001). These results demonstrate that, based on visual cues alone, horses exhibit physiological alertness toward potential predatory threats while responding to non-threatening stimuli with exploratory gaze behaviors.